The return of parliamentary life in Syria in 1954: historical study - Hamed, Ali Salih Hamdan (Al-Adab Journal, 2022)
Syria witnessed its first attempts to lay the foundations of the parliamentary system and activate its role in life in general in the late twenties of the last century, specifically during the French Mandate era (1920-1946). As soon as Syria became independent, it fell at the mercy of the military coups (1949-1954), which also faced the elected parliaments with iron and fire, according to their interests, without considering the interests of the helpless Syrian people. Syria witnessed a new phase of parliamentary life after the 1954 elections, following the fall of the military coups rule and the resignation of Adib al-Shishakli and his departure from the country. Various Syrian parties and independent personalities participated in the elections and the army did not interfere in state affairs, in a dangerous precedent, which led to a natural and free counting of votes. For the first time, therefore, the Syrian Parliament elections in 1954 can be counted as one of the fairest and most mature elections in the Arab countries at that time, which demonstrated the ability of the Syrians to choose their true representatives whenever the appropriate environment is available without the blatant interference of the influential authorities.